Cerebrospinal fluid concentrations of interleukin-1 beta, tumour necrosis factor-alpha, and interferon gamma in bacterial meningitis. Issue 2 (February 1994) - Ohga, S; Aoki, T; Okada, K; Akeda, H; Fujioka, K; Ohshima, A; Mori, T; Minamishima, I; Ueda, K
Abstract : To investigate the role of the inflammatory cytokines, the cerebrospinal fluid concentrations of interleukin (IL)-1 beta, tumour necrosis factor-alpha (TNF-alpha), and interferon gamma (IFN-gamma) were measured in 11 children with bacterial meningitis and two with mycoplasmic meningoencephalitis and compared with those in 50 children with aseptic meningitis and 15 with non-pleocytotic cerebrospinal fluid. Concentrations of IL-1 beta and TNF-alpha were each significantly higher in the cerebrospinal fluid of patients with bacterial meningitis than in those with aseptic meningitis or those with non-pleocytotic cerebrospinal fluid. IFN-gamma was detected at low concentrations in the cerebrospinal fluid of only 2/11 of those with bacterial meningitis. On the other hand, the IFN-gamma concentration was the highest in the cerebrospinal fluid of patients with aseptic meningitis. These results suggest that the inflammatory cytokines are differently released in the intrathecal space infected with viruses or bacteria.